Penyuluhan Hukum tentang Pemahaman Hak Pengelolahaan Wisata Pantai di Maluku - Sri Rumada Sihite (Karunia: Jurnal Hasil Pengabdian Masyarakat Indonesia, 2024)
Management rights originating from customary land are also found in the Maluku region, but it is determined that tourism management is one of the efforts made by the community and the government in preserving tourism objects. However, in the management of tourism itself, it is necessary to pay attention to the welfare of the community and the allocation of management rights granted in accordance with Article 7 of PP No. 18 of 2021 concerning management rights, land rights, apartment units, and land registration. This is what, This is what underlies the author to conduct legal counseling on understanding the management rights of dimaluku beach tourism.